Efektivitas Variety Show Program Keluarga Berencana Melalui Media Televisi - Damayanti .; Amiruddin Saleh; Richard W.E. Lumintang (Institut Pertanian Bogor, 2012)
ABSTRACT The study intended to determine and analyze the effectiveness of variety show family planning television program among teenagers. The variables were communicator characteristics, message, media and communican aspects. Those aspec were analyzed partially and simultaneously. the study was located at SMAN 4 Depok, West Java, during April 2012. The study was designed by using quasi-experimental method with explanative correlations. Sampling method was simple random method. Respondens was totally 80 students, devided into two groups: 40 students as a control group, and 40 students was treated. Data was analyze by descriptive frequency, Path analysis, t test, and Kendall’s tau b correlation. Result study indicated the program was highly effective. The treated group indicated more aware about family planning program than the control group was. The treated group has more averaged cognitive, affective and conative level than the control group. Meanwhile the communicator characteristics, messages, media and communicant aspect explained the program was more effective for teens, as well as the content, media and communicants aspects. In case of communicans aspect, merely the message influenced. Keywords: effectiveness, varietyshow, family planning television program